Transformation of Hydroacoustic Energy into Seismoacoustic Energy at 22 Hz in Medium Depth- and Deep-Sea Conditions - Grigory Dolgikh; Mikhail Bolsunovskii; Sergey Budrin; Stanislav Dolgikh; Mikhail Ivanov; Vladimir Ovcharenko; Aleksandr Pivovarov; Aleksandr Samchenko; Vladimir Chupin; Igor Yaroshchuk (Applied Sciences)
This work is devoted to an experiment studying the regularities of the propagation of hydroacoustic low-frequency signals in the conditions of the sea at intermediate depth and deep in terms of their transformation into vibrations in the upper layer of the Earth’s crust. This experiment belongs to the field of acoustic tomography and is aimed at solving the problems of non-contact methods for studying the geological structure of the shelf areas of the World Ocean. The novelty and uniqueness of the work lies in the use of a harmonic low-frequency hydroacoustic signal with a frequency of 22 Hz of high power, capable of creating Rayleigh surface waves at the “water–bottom” interface. The surface waves propagating at the bottom are registered by a coastal laser-interference measuring system capable of recording deformations in the upper crustal layer with an accuracy of 0.01 nm. The experimental results showed that the radiated hydroacoustic energy is not localized in the liquid half-space and propagates predominantly according to the law close to spherical divergence, even when the shelf depth is comparable to the wavelength of the radiated signal.